Analisis Penerapan Akuntansi Manajemen dalam Perencanaan dan Pengendalian Anggaran pada PT Wahana Interfood Nusantara Tbk Tahun 2020-2024 - Yohanes Cantus Firmus Luahambowo; Josh Billiam G. Bu’ulolo; Prakoso Nugroho; NuruL Dzuriah K.h; Hendra Lesmana (Politeknik Negeri Padang, 2026)
This study examines the implementation of management accounting in budgeting planning and control at PT Wahana Interfood Nusantara Tbk for the period 2020–2024. The research also evaluates the factors influencing its effectiveness and the impact on financial performance, measured using the Return on Assets (ROA). The study applies a descriptive qualitative approach with a case study design, using secondary data from the company’s Annual Reports and supporting documents. Data were analyzed through data reduction, presentation, and conclusion drawing, while profitability was assessed using ROA by comparing net profit with total assets. The results indicate that budgeting planning is conducted systematically using both top-down and bottom-up approaches, while control is implemented through periodic evaluations and variance analysis. However, deviations occurred due to market and cost fluctuations. The findings also show that implementation effectiveness is affected by organizational structure, human resource capability, information systems, and external factors. Overall, management accounting has contributed positively to budgeting processes, though further improvement in cost control and information quality is needed.